Optimization of the Role of Intelkam Unit in Early Detection for Preventing Theft of Motorcycles Belonging to Students in the Jurisdiction of Polrestabes Semarang - Fudhail, Nizham Tsauban (Advances in Police Science Research Journal, 2024)
The rise of criminal acts, especially theft belonging to students, which increases every year and is of concern to the performance of the intelligence unit, especially in early detection, which makes the police's performance certainly not optimal without involving all related functions and agencies and also support from all levels of society and working closely with all stakeholders. local government interests. The problem that occurred in the Semarang Polrestabes Police Intelligence Unit was something related to investigative procedures that were still not optimal and were not in line with the guidelines for the 2013 Police Intelligence Security Head Regulation which regulates Intelligence activities for the Indonesian National Police. This study uses a qualitative research approach to explore and understand the meaning of social problems. Data collection methods used are observation, interviews and document studies. From the results of the analysis carried out, the role that is recommended or expected is the role that should be carried out by the Semarang Police Intelligence Unit, especially in early detection of criminal acts of theft belonging to students.